Aspergillus fumigatus binding IgA and IgG1 are increased in bronchoalveolar lavage fluid of horses with neutrophilic asthma - Jentsch, Maria-Christin; Keilhaue, Aline; Wagner, Bettina; Rhyner, Claudio; Lübke, Sabrina; Karagulyan, Mariam; Arnold, Corinna; Lohmann, Katharina L.; Schnabel, Christiane L. (Frontiers in Immunology, 2024)
Introduction: Equine asthma (EA) is a common lower airway disease in horses, but it is ambiguous whether its pathogenesis is allergic. Extrinsic stimuli like hay dust induce acute exacerbation of clinical signs and sustained local neutrophilic inflammation in susceptible horses. Aspergillus (A.) fumigatus is an EA stimulus, but it is unclear if it merely acts as an IgE-provoking allergen. We aimed to comprehensively analyze immunoglobulin (Ig) isotypes in EA, elucidating their binding to different A. fumigatus antigens, and their quantities systemically in serum and locally in bronchoalveolar lavage fluid (BALF). Methods: Serum and BALF from healthy horses (HE, n=18) and horses with mild-moderate (MEA, n=20) or severe asthma (SEA, n=24) were compared. Ig isotype (IgG1, IgG3/5, IgG4/7, IgG6, IgA, IgE) binding to nine antigens (A. fumigatus lysate, and recombinant Asp f 1, Asp f 7, Asp f 8, dipeptidyl-peptidase 5, class II aldolase/adducin domain protein, glucoamylase, beta-hexosaminidase, peptide hydrolase) was compared by enzyme-linked immunosorbent assays. Total Ig isotype contents were determined by bead-based assays. Results: MEA and SEA differed from HE but hardly from each other. Compared to HE, asthmatic horses showed increased anti-A. fumigatus binding of IgG (BALF, serum) and IgA (BALF). Serum and BALF IgE binding and total IgE contents were similar between HE and EA. Single antigens, as well as A. fumigatus lysate, yielded similar Ig binding patterns. Serum and BALF IgG1 binding to all antigens was increased in SEA, and to several antigens in MEA. Serum IgG4/7 binding to two antigens was increased in SEA. BALF IgA binding to all antigens was increased in SEA and MEA. Total BALF IgG1 and IgG4/7 contents were increased in SEA, and serum IgG4/7 content was increased in MEA compared to HE. Yet, total isotype contents differentiated EA and HE less clearly than antigen-binding Ig. Discussion: A. fumigatus immunogenicity was confirmed without identification of single dominant antigens here. A. fumigatus provoked elevated BALF IgG1 and IgA binding and these isotypes appear relevant for neutrophilic EA, which does not support allergy. BALF Ig isotype differentiation beyond IgE is crucial for a comprehensive analysis of immune responses to fungi in EA pathogenesis.